If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + 24x = 22 + 25x Solving 27 + 24x = 22 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 27 + 24x + -25x = 22 + 25x + -25x Combine like terms: 24x + -25x = -1x 27 + -1x = 22 + 25x + -25x Combine like terms: 25x + -25x = 0 27 + -1x = 22 + 0 27 + -1x = 22 Add '-27' to each side of the equation. 27 + -27 + -1x = 22 + -27 Combine like terms: 27 + -27 = 0 0 + -1x = 22 + -27 -1x = 22 + -27 Combine like terms: 22 + -27 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 3(2x-3)=0 | | c=4a+2 | | c=4a-2 | | (3x+8)(5x+7)=0 | | 2*4+7-6= | | 2w+2=p | | 12x-17y-6x+7y= | | x/9=8=8 | | a+18=37 | | 5x(7-x)=0 | | 6x-5=22 | | 6x+3=-15-3x | | Q=4T+3R | | 4x+2x+10=52 | | 4/6=n/9 | | 7/7m=9 | | y+1=-(x+6) | | 8/18=n/5 | | 6(p+3)+5=3(2p+4)-4p | | 5x+x=1890 | | (4-7x)*(4-7x)=81 | | x^2=(y+3.5) | | n/3=6/18 | | 3*2*8-4= | | 13x^2-250x+600=0 | | 3(2x+7)=3x+6 | | 4*x+x=34 | | 11=x+22 | | 2(2x+3)=(x+1.4)+0.1 | | 1/0.4(20) | | 8x+5=5x+14x-3 | | 3(2x+7)=3(x+7) |